Supplemental dose of antithrombin use in disseminated intravascular coagulation patients after abdominal sepsis - Tagami, Takashi; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo (Thrombosis and Haemostasis, 2015)
The effectiveness of supplemental dose antithrombin administration (1,500 to 3,000 IU/ day) for patients with sepsis-associated disseminated intravascular coagulation (DIC), especially sepsis due to abdominal origin, remains uncertain. This was a retrospective cohort study of patients with mechanically ventilated septic shock and DIC after emergency surgery for perforation of the lower intestinal tract using a nationwide administrative database, Japanese Diagnosis Procedure Combination inpatient database. A total of 2,164 patients treated at 612 hospitals during the 33-month study period between 2010 and 2013 were divided into an antithrombin group (n=1,021) and a control group (n=1,143), from which 518 propensity score-matched pairs were generated. Although there was no significant 28-day mortality difference between the two groups in the unmatched groups (control vs antithrombin: 25.7 vs 22.9 %; difference, 2.8 %; 95 % confidence interval [CI], –0.8–6.4), a significant difference existed between the two groups in propensity-score weighted groups (26.3 vs 21.7 %; difference, 4.6 %; 95 % CI, 2.0–7.1) and propensity-score matched groups (27.6 vs 19.9 %; difference, 7.7 %; 95 % CI, 2.5–12.9). Logistic regression analyses showed a significant association between antithrombin use and lower 28-day mortality in propensity-matched groups (odds ratio, 0.65; 95 % CI, 0.49–0.87). Analysis using the hospital antithrombin-prescribing rate as an instrumental variable showed that receipt of antithrombin was associated with a 6.5 % (95 % CI, 0.05–13.0) reduction in 28-day mortality. Supplemental dose of antithrombin administration may be associated with reduced 28-day mortality in sepsis-associated DIC patients after emergency laparotomy for intestinal perforation.
Keywords: Antithrombin; disseminated intravascular coagulation; sepsis; surgery